Effects of accumulated cyanobacterial bloom biomass contents on the characteristics of surface fluid sediments in a eutrophic shallow lake. (15th April 2022) - Wang, Chunliu; Xu, Da; Bai, Leilei; Zhu, Bosong; Huang, Lei; Jiang, Helong
Abstract : In eutrophic shallow lakes, cyanobacterial blooms will occur frequently and then accumulate on sediments, leading to the variation in the surface sediment properties. In this study, the influence of accumulated cyanobacterial blooms biomass (CBB) content on surface sediment properties was determined in microcosm experiments through monitoring surface sediment physicochemical and rheological properties. During one-month incubation, it was found that surface sediment volume increased, and the density decreased from 1.36 g cm −3 to 1.13 g cm −3 with increase in accumulated CBB contents. The results of particle size distribution indicated that CBB accumulation in sediments led to sediment flocculation and agglomeration. In the meantime, there were high ratios polysaccharide/protein in extracellular polymeric substances (EPS) with a decrease in bound EPS/colloid EPS under high CBB contents, which enhanced the sediment particle agglomeration and reduced fluid sediment stability. Further, the critical shear stress in rheological test for sediments on day 30 presented an exponential decay ( R 2  = 0.97) with increase in accumulated CBB contents. And a threshold value at 0.15% accumulated CBB content indicated sediments could be resuspended easier when accumulated CBB content was higher than 0.15%. Altogether, this study showed that the accumulated CBB content had a strong influence on surface fluid sediment properties. The results were important in sediment management since CBB affects sediment suspension for eutrophication shallow lakes. Graphical abstract: Image 1 Highlights: The accumulation of CBB in sediment led to the formation of fluid sediment. Sediment density showed an exponential downward trend with accumulated CBB content. The variations in EPS related to the formation and stability of fluid sediment. Sediment density and EPS properties influenced critical shear stress of fluid sediment. Sediment suspended easier when accumulated CBB content was more than 0.15%.